2011
DOI: 10.1007/s00167-011-1837-x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma intra-articular injections for cartilage degeneration and osteoarthritis: single- versus double-spinning approach

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
322
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(346 citation statements)
references
References 35 publications
12
322
2
10
Order By: Relevance
“…No major complication such as deep infection, muscle atrophy, deep vein thrombosis, fever, hematoma, tissue hypertrophy, adhesion formation, or other major adverse events occurred among study subjects. Similar studies by Sampson S et al [6] , Filardo G et al [7] , Kon E et al [5] , Sun Y et al [8] and Giannini S et al [9] showed no major complication or adverse effects. In our study, three cases in GFRP group showed temporary worsening of pain for about 24 hours which resolved spontaneously.…”
Section: Discussionsupporting
confidence: 80%
“…No major complication such as deep infection, muscle atrophy, deep vein thrombosis, fever, hematoma, tissue hypertrophy, adhesion formation, or other major adverse events occurred among study subjects. Similar studies by Sampson S et al [6] , Filardo G et al [7] , Kon E et al [5] , Sun Y et al [8] and Giannini S et al [9] showed no major complication or adverse effects. In our study, three cases in GFRP group showed temporary worsening of pain for about 24 hours which resolved spontaneously.…”
Section: Discussionsupporting
confidence: 80%
“…No major complication such as deep infection, muscle atrophy, deep vein thrombosis, fever, hematoma, tissue hypertrophy, adhesion formation, or other major adverse events occurred among study subjects. Similar studies by Sampson S et al [6] , Filardo G et al [7] , Kon E et al [5] , Sun Y et al [8] and Giannini S et al [9] showed no major complication or adverse effects. In our study, three cases in GFRP group showed temporary worsening of pain for about 24 hours which resolved spontaneously.…”
Section: Discussionsupporting
confidence: 72%
“…30 Both studies showed no significant changes between groups. These studies emphasize the fact that current literature is lacking randomized controlled studies aimed to introduce the optimal PRP treatment (preparation characteristics, administration protocol, etc.)…”
Section: Discussionmentioning
confidence: 88%
“…These included local pain, stiffness, syncope, dizziness, headache, nausea, sweating, and tachycardia, all self-limited. Filardo et al 30 reported temporary pain and swelling reaction for the PRP treatment (number of patients not mentioned). Spakova et al 32 documented temporary mild worsening of pain in the knee joint after application of PRP in 6 cases (out of 60), which was spontaneously resolved after 2 days.…”
Section: Adverse Effectsmentioning
confidence: 99%